PALESTINIAN RESISTANCE IN MAHMUD DARWISH'S BITHOQOH HUWIYYAH POEM: A KINAYAH STUDY - Mellinda Raswari Jambak; Muassomah Muassomah; Alam An Shori; Nabila Nur Khonsa; Aldrian Aldrian (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2024)
This research explores indirect expression in Mahmoud Darwish's poem